New proposal to express notch stress approach results by equivalent SCFs. (February 2019) - Schaumann, P.; Schürmann, K.
Highlights: Concept to transform notch stress approach (NSA) results in equivalent SCFNSA . SCFNSA are equivalent to SCFs based on structural stress approach (SSA). Comparison of both approaches on structural stress level for tubular X-joint. Integrating NSA within SSA based fatigue design formalism of welded structures. Combining benefits of both approaches within SSA based software tools. Abstract: For the fatigue design of welded structures, such as jacket substructures for offshore wind energy turbines, the structural stress approach is state of the art. Standards and guidelines also allow the application of the notch stress approach for complex welded components, weld roots, or to consider the advantages of the real weld geometry if measured or after grinding within the fatigue design. Since the theoretical background as well as the application of both approaches differs widely, it is not possible to directly integrate the fatigue notch factor Kf according to the notch stress approach into the design formalism of the welded structures based on the structural stress approach. Therefore, this paper derives a methodology to transform the elastic fatigue notch factor Kf into an equivalent stress concentration factor. By applying the introduced concept design engineers are able to selectively combine the advantages of both approaches without adapting the approved software tools to perform the fatigue design of complete welded structures. Furthermore, the presented concept of the equivalent stress concentration factor is an effective tool to perform a direct comparison of the relative fatigue resistance according to both approaches – structural stress approach and notch stress approach – on structural stress concentration level rather than on the level of damages or lifetime. This opportunity of comparison is applied on a tubular X-joint of a jacket substructure. The computed stress concentration factors are in good accordance between both approaches which is similar to the lifetime based results given in literature for application of both approaches on tubular K- and Y-joints.